Snap-Through and Mechanical Strain Analysis of a MEMS Bistable Vibration Energy Harvester - Masoud Derakhshani; Thomas A. Berfield (Shock and Vibration)
Vibration-based energy harvesting via microelectromechanical system- (MEMS-) scale devices presents numerous challenges due to difficulties in maximizing power output at low driving frequencies. This work investigates the performance of a uniquely designed microscale bistable vibration energy harvester featuring a central buckled beam coated with a piezoelectric layer. In this design, the central beam is pinned at its midpoint by using a torsional rod, which in turn is connected to two cantilever arms designed to induce bistable motion of the central buckled beam. The ability to induce switching between stable states is a critical strategy for boosting power output of MEMS. This study presents the formulation of a model to analyze the static and dynamic behaviors of the coupled structure, with a focus on the evolution of elongation strain within the piezoelectric layer. Cases of various initial buckling stress levels, driving frequencies, and driving amplitude were considered to identify regimes of viable energy harvesting. Results showed that bistable-state switching, or snap-through motion of the buckled beam, produced a significant increase in power production potential over a range of driving frequencies. These results indicate that optimal vibration scavenging requires an approach that balances the initial buckling stress level with the expected range of driving frequencies for a particular environment.